Dynamic Capabilities: A Review of Past Research and an Agenda for the Future - Barreto, Ilídio (Journal of Management, 2010)
The dynamic capabilities view, by addressing the question of how firms can cope with changing environments, has gained increasing attention in the management literature in recent years, not only in the concept’s original domain (strategic management) but also in many other areas within business administration. However, such remarkable growth has been associated with a proliferation of definitions of the focal construct as well as the emergence of a complex and disconnected body of research. In addition, the approach has also received some recurring criticisms. In this study, the author reviews the diverse research streams on dynamic capabilities, identifies main limitations and challenges, suggests a new conceptualization of dynamic capability as an aggregate multidimensional construct, and provides guidance about promising avenues for future research.